Building of Family-based Islamic Character for Children in Tablighi Jamaat Community - Engkizar Engkizar; Munawir K; Soni Kaputra; Zainul Arifin; Syafrimen Syafril; Fuady Anwar; Mutathahirin Mutathahirin (Ta'dib, 2021)
This study is aimed at exploring how to build family-based Islamic character in the Tablighi Jamaat community.  As a qualitative study, the research was conducted by using an ethnographic approach. The data were collected through direct interviews with ten informants which are the heads of the family that belong to the Tablighi Jamaat community. Moreover, the researcher was also involved in some religious activities of the community for two years that the observation during the activities can be used to reinforce the result of the interviews. Those activities are Ijtima’ (annual gathering), Bayan Markas (sermon), Ta’lim Halaqah, Khuruj (proselytizing tour), Jaulah, and some informal visits to interviewees’ families. All data, both interviews and direct observation, were thematically analyzed by using specific software, namely NVivo 12. Based on the data it is found that there are five major Islamic characters could be developed through the family-based character building in the Jama’ah Tablghi community, namely: (1) good moral conduct to parents, (2) having a sense of shame to violate the shari’a, (3) behaving based on Islamic shari’a, (4) time punctuality, (5) good moral characters. Finally, the findings reveal that the building of family-based Islamic characters in the Tablighi Jamaat community contributes to the positive effects of children's Islamic characters in family and community.